The Reconstruction of Javanese Tradition: A Literary Anthropological Study of Serat Prabangkara - Mochamad Syahrul Iqbal; Suwardi Endraswara; Sri Harti Widyastuti (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
The Prabangkara Manuscript or Serat Prabangkara by Ki Padmasusastra is one of the notable Javanese literary works that captures the social and cultural transformations during Indonesia’s colonial transition. Serat Prabangkara is one of the Javanese literatures works steeped in local representations of tradition. This paper explores how text portrays royal court life, marriage arrangement, and the use of occult practices, as well as reconstructing traditions of harmony trough thematized of love, social hierarchy, gender relations, and nature symbolism. A literary anthropological approach is utilized to examine the text within the Javanese cultural context. Within the framework of literary anthropology, the study of Serat Prabangkara serves as a medium to comprehend how Javanese tradition is reconstructed and preserved through literary narrative. This theory frames literary works as a cultural representation, which enables in-depth analysis of the traditional aspects embodied in it. The study result revealed that Serat Prabangkara serves as a medium for tradition preservation as well as cultural value adaptation in a modern context. The symbolism in text reflects universal values of balance, love, and harmony that remain relevant across different periods.